Evaluation of physically modified kenaf core adsorbent for carbon dioxide adsorptive study. Issue 1 (1st April 2022) - Nurhidayah, A; Zaini, N; Zulhaziman, M; Salleh, M; Zulbadli, N; Mohamad, Noor Ashikin; Ezaty, S N; Shafie, N S; Sahri, Dzulkarnain Mohd; Mohd Najib, Siti Sarah Aliah
Abstract: This paper evaluates on the capability of kenaf core (Hibiscus Cannabinus L.) material as the proposed solid adsorbent for CO2 adsorption study via physical treatment modification. The proposed physical treatment was successfully conducted by undergoing two stages of carbonization and activation treatment to improve the pore development structure of the material. The carbonized kenaf core (CKC) was prepared by carbonizing the raw kenaf core (RKC) at 800°C with constant nitrogen flow for 5 hours. Activation process took placed by impregnating KOH in the furnace with alternately switching to CO2 up to 800C for 2 hours. The morphological and structural characterization studies were conducted using Field Emission Scanning Electron Microscope (FESEM) and Fourier Transform Infrared Spectroscopy (FTIR). The CO2 adsorption process was carried in the gravimetric analyzer by varying the effect of bed pressure and gas flowrate. This study revealed that the AKC has the highest CO2 adsorption capacity of 1.70 mmol/g (1 bar) and 2.85 mmol/g (30 bar). Based on the morphology, AKC demonstrated better small micropore development that helps in providing a larger adsorption site; hence attributes to the higher CO2 adsorption capacity. This study contributes to the development of knowledge on enhancing the CO2 adsorption on the physically-modified kenaf core material that would be used as an alternative material for CO2 adsorbent.